The Harmonization of Technical Barriers to Trade, Innovation and Export Behavior: Theory with an application to EU Environmental Data - Andrea Mantovani; Mark Vancauteren (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
A key feature of the EU harmonization of technical barriers to trade (TBT's) is that exporting firms may entail a compliance costs. This paper provides theoretical and empirical work. In a simple Cournot duopoly with trade, we pursue the idea that process R&D has a positive spillover effect (with different intensities) in lowering the compliance cost and investigate the impact of an R&D subsidy. Using a self-constructed database, which specifically identifies sectors where the EU has sought to introduce harmonized environmental regulations, we find evidence that support this prediction of the theory.
Keywords: 330